Terras nas mãos dos pequenos: relações produtivas e econômicas dos pequenos produtores de cana para as usinas de açúcar e álcool do interior paulista - Roviero, Andréia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to understand, map and discuss the situation of the small sugarcane producer and the thematic that surround it, starting from the looks of sociology and rural anthropology. The farmer considered as small, are most in the state of São Paulo. The research methodology is qualitative. So through the application of semi-structured questionnaires, we seek to understand more about the universe and profile of rural agent. Were interviewed 40 small producers sugarcane in the municipalities headquarters of rural development offices - EDR - the central region of São Paulo, Jaboticabal and Araraquara. The objective is to understand the relationship of the producers with their land ownership, productions, choices, sociability with plants and other areas frequented by them between other questionings that reveal and help understand who is the small sugarcane producer of central State. For this, we required investigate how established the production of cane sugar in the state, with its history, challenges and impacts. Sugarcane production generates various controversies and defenses, both in the economic area and in the environmental. The actual reality of cane sugar triggers the need to rescue as his installation as main crops produced in the state of São Paulo, and understand the role of small farmers in the socioeconomic context of the central region of the state. At this juncture, are present mentions of rural universe. Be on souvenir production of a time of more contact with the rural environment, or even rural ties that were taken to the urban, since there is a feeling of belonging and connection to the land, regardless of culture produced at the moment. The field research revealed of the fact that the cane sugar, a fully oriented production for ethanol industry, did not invalidate the affection and connection to the land maintained by smallholders. The economic factor, a number of factors that carried them to the choice to ...

Esta pesquisa tem o propósito de mapear, discutir e entender a realidade do pequeno produtor canavieiro do Estado de São Paulo, a partir dos olhares da sociologia e da antropologia rural. Os pequenos agricultores são maioria no interior do Estado de São Paulo. A metodologia desta pesquisa é qualitativa, mas foram também produzidas amostragens estatísticas. Assim, a partir da aplicação de questionários semiestruturados, buscamos compreender o universo e o perfil desse agente produtivo. Foram entrevistados 40 pequenos produtores canavieiros, em duas sedes municipais dos escritórios de desenvolvimento rurais (EDR) da região central do Estado de São Paulo: Jaboticabal e Araraquara. A partir dessas entrevistas, procuramos entender a relação dos produtores com a propriedade da terra. Além disso, buscamos analisar as produções e as escolhas dos produtores estudados de acordo com a sua sociabilidade com relação às usinas e aos demais espaços frequentados por eles. Produzir cana-de-açúcar gera controvérsias, tanto no terreno econômico, quanto no ambiental e social. A realidade da cana desencadeia, pois, a necessidade de se resgatar a sua história, investigando, sobretudo, como se deu o processo que tornou a cana a principal cultura produzida no Estado de São Paulo. É por isso que este trabalho também tem uma seção dedicada ao histórico da produção de cana-de-açúcar no Estado. Nessa seção, arrolamos os principais desafios e impactos envolvidos na produção de cana-de-açúcar, e também buscamos compreender o papel do pequeno produtor, no contexto socioeconômico da região central desse Estado, ao longo dos últimos anos. Nessa conjuntura, estão presentes valores ligados à sociedade rural, sobretudo no que diz respeito às lembranças de uma época em que o contato com o campo era diário. Constatamos que, mesmo nos casos em que os produtores foram levados para um outro modelo de realidade, ainda existe um...
Keywords: Agricultura - Aspectos sociais; Pequenos produtores - Aspectos sociais; Cana-de-açúcar; Agriculture Social aspects